INDONESIA NATIONAL SPORTS GAMES (PON) ORGANIZING IN THE REFORM ERA (2000-2020) - Putra, Panji Rinaldi; Ma’mun, Amung; Firmansyah, Helmy (ASEAN Journal of Sport for Development and Peace, 2022)
This research focuses on organizing the Indonesia National Sports Games (PON) in the reform era. The organizing of the Indonesia National Sports Games (PON) is an effort made by the Indonesian government in developing sports and attracting potential athletes from all over Indonesia. This study aims to find out how the organizing of the Indonesia National Sports Games (PON) in the reform era from PON in 2000 in East Java to PON in 2020 in Papua and also, to find out how the development of sports and match numbers in PON in the reform era. The method used in this study is the historical method which starts from the first step, namely heuristics, criticism, interpretation, and historiography. This research uses literature study and analysis of print and electronic media as data collection procedures. This study discusses the implementation of PON in the reform era, which became a turning point in the development of sports in Indonesia. The results of this research are that the addition of match numbers and sports branches is closely related to the organizers' interests. The development of game numbers is very uncontrollable from PON 2000 to PON 2020.